Qualitative research: An ongoing methodology on social facts - Hernández Arteaga, Isabel (Rastros Rostros, 2012)
This review article is the result of experience on the comprehension of the social phenomenon from the point of view of qualitative research. This work seeks to explain the reflexive dynamics that characterize the process of learning, analysis, comprehension, and interpretation of social reality that is traversed by relationships between individuals. The employed method is mainly determined by the manner in which the research project is approached and by the quest for answers. Referenced sources are part of an array of authors that are read by teachers and researchers during their formation, a plane in which discussion is brought to life when the educator contemplates the possibility of considering men in their context facing the world.
Keywords: Flexibility; Social fact; Qualitative research; Research process